APPLICATION OF B.F. SKINNER'S BEHAVIORISM LEARNING THEORY IN ISLAMIC EDUCATION LEARNING FOR HIGH SCHOOL STUDENTS - Yuli, Yunita Nita; Firmansyah, Alfitra; Muqowim, Muqowim; Nurdin, Muhammad Alwi (Jurnal Ilmiah Didaktika, 2024)
This study aimed to know and describe the application of B.F Skinner's Operant Conditioning Behaviorism Learning Theory in Islamic Education learning at high school students and to know students' responses. In this study, the researchers described the forms of stimulus provision and the principles of Operant Conditioning B.F Skinner applied in Islamic Education learning. This research used qualitative methods. The data collection techniques used observation, interviews, and documentation. While data analysis is done with several stages, namely data reduction, data presentation, and conclusion drawing. The results showed that B.F Skinner's Operant Conditioning Behaviourism Learning Theory in Islamic Education learning was successfully applied. The implication of this research shows that overall the application of the theory resulted in a good response and changes in student behaviour in a positive direction in the form of the formation of learning motivation, activeness, reinforcement and improved student memory.